PENGARUH MOTIVASI KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI DPRD KABUPATEN KUTAI TIMUR - Suyatin, Rama Fadli Elfreda Aplonia Lau (EKONOMIA, 2016)
RAMA Fadli , Influence Motivation , Communication and Leadership Style Discipline Employee Work Against East Kutai Regency under the guidance of Mrs. Elfreda A. Lau as a Supervisor I and Mrs. Suyatin as Advisor II .             This research background by the fact that indicates the existence of various obstacles in improving labor discipline of employees , efforts to improve the Work Discipline Employees Regency of East Kutai heavily influenced by variables motivation , communication and leadership style , which can affect performance , so that someone is willing work to earn a larger salary . From the description of the background issues as outlined , defined formulation of the problem : 1.      Does the variable motivation, communication and leadership style affect siqnifikan to the discipline of employees working in the Office of the East Kutai Regency ? 2.      Which of the variables of motivation, communication and leadership style dominant influence on the discipline of employees working in the Office of the East Kutai Regency ?             Management is a special process of planning , organizing , implementing, and monitoring performed to determine as well as the achievement of targets that have been determined through the use of human resources and others.             Basic hypothesis proposed in this research is variable Motivation, Communication and Leadership Style significant effect Against Employees At Work Discipline Office of the East Kutai Regency , and the motivation variable dominant influence on Employees At Work Discipline Office of the East Kutai Regency .             The conclusions of this study are motivation , communication , and leadership style has a significant influence on the Work Discipline Employees At the Office of East Kutai Regency . This proves that the first hypothesis of the three variables , together affect the Work Discipline Employees At Parliament Office East Kutai proven true , and among these three variables , communication has the most significant effect on Work Discipline Employees At Parliament Office Kutai east so that the second hypothesis is rejected .